Warm-up with baseball bats of varying moments of inertia: effect on bat velocity and swing pattern - Southard, D.; Groomer, L. (Research Quarterly for Exercise and Sport, 2003)
The purpose of this study was to determine if warm-up with baseball bats of different moments of inertia has an effect on swing pattern and bat velocity. Ten experienced baseball players (ages 20-25 years) voluntarily participated in this study. Each participant was required to complete 10 dry swings (5 warm-up and 5 postwarm-up) at maximum effort within 3 different conditions. Post warm-up was always with a standard bat (I = .27 kgm2; 83.8 cm, 9.1 N). Warm-up for Condition 1 was with the standard bat. Condition 2 required participants to warm up with a standard bat plus a 6.1 N lead donut (I = .49 kgm2, 83.8 cm, 15.6 N). Condition 3 required participants to warm up with a hollow plastic bat (I = .08 kgm2; 83.8 cm, 3.34 N). Quantitative and qualitative analyses indicated that following warm-up with the weighted bat (largest moment of inertia), swing pattern was significantly altered, and post warm-up velocity was the lowest of the three conditions.